Search for lepton-flavour-violating H → μτ decays of the Higgs boson with the ATLAS detector - Santos, S. P. Amor dos (2015)
A direct search for lepton-flavour-violating H → μτ decays of the recently discovered Higgs boson with the ATLAS detector at the LHC is presented. The analysis is performed in the H → μτhad channel, where τhad is a hadronically decaying τ -lepton. The search is based on the data sample of proton-proton collisions collected by the ATLAS experiment corresponding to an integrated luminosity of 20.3 fb−1 at a centre-of-mass energy of TeV. No statistically significant excess of data over the predicted background is observed. The observed (expected) 95% confidence-level upper limit on the branching fraction, Br(H → μτ ), is 1.85% (1.24%).